Kebijakan Pajak Di Indonesia Mengenai Belanja Online - Arrum Widowati (Universitas Katolik Soegijapranata, Semarang, 2022)
At this time, people are increasingly familiar with using technological advances because it is considered easier and more practical, especially in today's digital era. Due to the increasingly digital era, where many activities can be done via the internet as well as shopping. Now shopping for the desired items from anywhere can be purchased through online shopping, but what is the tax policy if we do online shopping. In this article, we will discuss the imposition of taxes on goods purchased through online shopping, whether these goods are taxable or not and how much tax rates apply to both imported goods and goods from local stores